Review on Common Steganography Techniques (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Various authorities are keen to preserve the confidentiality of their information and protect it from competing or hostile parties who were also keen to access that information by all available means. Since the encryption of information is exposed as it produces incomprehensible texts that arouse suspicion, some tend to work in a way that removes suspicions by hiding the information in a medium like text or picture so that what is sent and circulated appears natural and free of signs or incomprehensible symbols as if not loaded with any additional information. This paper introduces a review the techniques used to hide data in images as one of the most common concealment techniques.